Simplify 2(3v+9)−14−6(−5v−4) .(1 point)

1 answer

To simplify the expression, we need to distribute and combine like terms.

2(3v + 9) - 14 - 6(-5v - 4)

First, distribute 2 to (3v + 9) using the distributive property:
6v + 18 - 14 - 6(-5v - 4)

Next, distribute -6 to (-5v - 4):
6v + 18 - 14 + 30v + 24

Now, combine like terms:
(6v + 30v) + (18 + 24) - 14
36v + 42 - 14

Finally, combine remaining like terms:
36v + 28
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions